Synthesis, insecticidal activity, resistance, photodegradation and toxicity of pyrethroids (A review). (September 2020) - Zhu, Qiuyan; Yang, Yang; Zhong, Yingying; Lao, Zhiting; O'Neill, Paul; Hong, David; Zhang, Kun; Zhao, Suqing
Abstract: Pyrethroids are a class of highly effective, broad-spectrum, less toxic, biodegradable synthetic pesticides. However, despite the extremely wide application of pyrethroids, there are many problems, such as insecticide resistance, lethal/sub-lethal toxicity to mammals, aquatic organisms or other beneficial organisms. The objectives of this review were to cover the main structures, synthesis, steroisomers, mechanisms of action, anti-mosquito activities, resistance, photodegradation and toxicities of pyrethroids. That was to provide a reference for synthesizing or screening novel pyrethroids with low insecticide resistance and low toxicity to beneficial organisms, evaluating the environmental pollution of pyrethroids and its metabolites. Besides, pyrethroids are mainly used for the control of vectors such as insects, and the non-target organisms are mammals, aquatic organisms etc. While maintaining the insecticidal activity is important, its toxic effects on non-target organisms should be also considered. Pyrethroid resistance is present not only in insect mosquitoes but also in environmental microorganisms, which results in anti-pyrethroids resistance (APR) strains. Besides, photodegradation product dibenzofurans is harmful to mammals and environment. Additionally, pyrethroid metabolites may have higher hormonal interference than the parents. Particularly, delivery of pyrethroids in nanoform can reduce the discharge of more toxic substances (such as organic solvents, etc.) to the environment. Graphical abstract: Image 1 Highlights: The resistance, photodegradation, toxicity, mechanisms of pyrethroids is reviewed. Pyrethroid resistance in microbes can lead to anti-pyrethroids resistance strains. Pyrethroid metabolites may have higher hormonal interference than the parents. Photodegradation product dibenzofurans is harmful to mammals and the environment. Delivery of pyrethroids in nanoform reduces the discharge of more toxic substances.